2021
DOI: 10.3390/s21144683
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Video Game Addiction Using Heart-Rate Variability Parameters

Abstract: The purpose of this study is to determine heart rate variability (HRV) parameters that can quantitatively characterize game addiction by using electrocardiograms (ECGs). 23 subjects were classified into two groups prior to the experiment, 11 game-addicted subjects, and 12 non-addicted subjects, using questionnaires (CIUS and IAT). Various HRV parameters were tested to identify the addicted subject. The subjects played the League of Legends game for 30–40 min. The experimenter measured ECG during the game at va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Because the inspection of HRV involves noninvasive methods, those with substance use disorders could conduct self-assessments in their home environment [22]. HRV has been used as a biomarker for severe substance use disorder [18] and also as a useful biomarker for other addictions, such as video game addiction [23] and alcohol addiction. According to the results of this study, the biological HRV age may be more sensitive than traditional HRV parameters, such as LF and HF, to be a biomarker on addiction subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Because the inspection of HRV involves noninvasive methods, those with substance use disorders could conduct self-assessments in their home environment [22]. HRV has been used as a biomarker for severe substance use disorder [18] and also as a useful biomarker for other addictions, such as video game addiction [23] and alcohol addiction. According to the results of this study, the biological HRV age may be more sensitive than traditional HRV parameters, such as LF and HF, to be a biomarker on addiction subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, looking into the brain signal during the action of game playing was an inevitable step, despite the difficulty in controlling subjects during the experiment. Hafeez et al [ 12 ] and Kim et al [ 13 ] examined the bio-signals of IGD subjects during game playing and found significantly different EEG and ECG patterns in the IGD group compared to the healthy group. Moreover, the current study showed a 63.5%–73.1% accuracy in identifying the IGD subjects.…”
Section: Discussionmentioning
confidence: 99%
“…They reported an 86.9% (±9.49) detection rate in terms of the addicted group and an 88.0% (±10.41) detection rate in terms of the non-addicted group based on a θ parameter measurement at O2 (right occipital region). Kim et al [ 13 ] used heart rate variability (HRV) parameters to examine the patterns of players with gaming disorders during internet game playing. They used the IAT and CIUS tests to group the subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Study sample sizes ranged from 23 to 148 participants, while group sizes varied from 11 to 50 individuals per group. Only male participants were enrolled in seven out of 11 studies [28][29][30][31][32][33][34]. While three studies enrolled adolescents as well-two with a defined age range from 15 to 25 years [31,33] and one from 16 to 29 years [32], the rest involved adult participants only.…”
Section: Research Participants and Study Designmentioning
confidence: 99%